Cybersecurity Maturity Assessment of Information Systems for Yemen Telecoms - Abohatem , Abdulkarem Yahya; Ba-Alwi , Fadl Mutaher (International Journal of Intelligent Systems and Applications in Engineering, 2023)
With the use of several standards, this study seeks to ascertain Yemen Telecoms’ level of maturity and assess the efficacy of information systems protection. Specialist information and recurring technical reports were used to gather the data, which was then compared to the international standard required to determine the maturity level. Strong cybersecurity procedures must be in place since cybersecurity threats are becoming more frequent and complicated. Although Yemen Telecoms has put in place a number of cybersecurity measures, our analysis shows that its information system protection rules and procedures still have holes. Choosing the best cybersecurity framework will also be aided by the study. In order to effectively defend Yemen Telecoms against cyber threats, we offer suggestions for bolstering the cybersecurity information systems.